PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DENGANPEMBELAJARAN BERBASIS SCIENTIFIC APPROACH SISWA KELAS VIIISLTP SWASTA PARULIAN MEDAN - MARLINDOAMAN SARAGIH (JURNAL ILMIAH SIMANTEK, 2019)
Grade VIII students at Medan's private SLTP Parulian, have difficulty in understanding biology subjects. The method used in biology subjects still uses lecture methods and the low ability of students' thinking is due to the fact that learning biology has tended to only hone the aspects of remembering and understanding. This study aims to determine whether there is an influence of Scientific Approach-based learning on students' critical thinking skills. The variables in this study consisted of Scientific Approach-based learning as an independent variable, students' critical thinking skills as the dependent variable. Data collection method is to use the written test method in the form of a description of questions for critical thinking skills in accordance with indicators of students' critical thinking skills. The validity of this instrument uses the validity and reliability testing of items by testing the level of difficulty and distinguishing features of the questions. Data analysis techniques to test hypotheses using t-test analysis at a significance level of 5%. The results showed that the Scientific Approach-based learning had an effect on the critical thinking skills of students in the VIIISLTP Parulian Medan Private class, as evidenced by the results of using the statistical test, the t test. This proves that the use of Scientific Approach-based learning can be used in learning because it can have a positive and significant influence on students' thinking abilities